Novel compound for use as medicament for treatment of hypercholesterolemia and atherosclerosis - Abd. Shukor, Mohd. Yunus; Gunasekaran, Baskaran; Salvamani, Shamala; Azlan, Azrina; Abu Bakar @ Zakaria, Md Zuki; Ahmad, Siti Aqlima (2014)
The present invention provides a novel compound apigenin 5-O-a-arabinofuranosyl-8-C-b-glucopyranoside (AAG). AAG is usable for treatment or prevention of hypercholesterolemia and atherosclerosis. AAG can be isolated from an edible medicinal plant, Basella alba L. and was shown to be non toxic in cytotoxicity (in vitro), acute and sub-chronic toxicity studies (in vivo). The novel compound showed more than 80% inhibitory effect on activity of HMG-CoA reductase and able to treat hypercholesterolemia by lowering total cholesterol (TC), Low density lipoprotein (LDL) and triglyceride (TG) level in serum and significantly reduces the plaque formation in the aorta.